Physical-Mechanical Properties of Bamboo-Textile-Reinforced Polymer Made with Vacuum-Assist Resin Transfer Molding. Issue 17 (2nd December 2022) - Chang, Chun-Wei; Chang, Feng-Cheng
ABSTRACT: Bamboo fiber-reinforced polymers have been widely studied as natural fiber composites. This study fabricated a continuous bamboo-textile-reinforced polymer (BTRP) composite by using woven bamboo strips and epoxy through vacuum-assisted resin transfer molding (VA-RTM). The physical properties, including bulk density and equilibrium moisture content, of various BTRP specimens with different textile architectures, stacking sequences, loading axes, and numbers of layers were preliminarily evaluated. The specimens' flexural properties, including strength, modulus, integral load – deflection relationship, damage parameters, and fractography characteristics, were also examined. As the number of layers increased, the flexural strength decreased but modulus values increased. When the number of layers was constant, the plain-woven BTRP specimens had slightly higher strength and modulus values than did the twill-woven specimens. The BTRP specimens exhibited remarkable mechanical properties and staged failure behaviors unique to laminated materials. Moreover, the stiffness of the specimens was attenuated before reaching the ultimate load, which was attributed to microscopic interphase damage, and the various architectures affected the specimens' fracture modes. The gradual multistage failure modes of the specimens imply that the fabricated composite is relatively safe for use. According to these results, the fabricated composite incorporates the advantages of VA-RTM and continuous nontwisted bamboo strips, indicating that it has substantial commercial potential.